Tetramethylpyrazine supplementation reduced Salmonella Typhimurium load and inflammatory response in broilers. (20th March 2019) - Liu, N; Lin, L; Wang, J Q; Zhang, F K; Wang, J P
ABSTRACT: The present study tested whether tetramethylpyrazine (TMP) supplementation could influence the growth performance, Salmonella Typhimurium ( S . Typhimurium) load, inflammasomes, cytokines, and chemokines in broilers. Treatments were a 2 × 2 factorial design, including negative control (NC), S. Typhimurium challenge (SC), and NC/SC + TMP (150 mg/kg of diet). The trial lasted for 28 D, and S. Typhimurium subclinical challenge was occurred on day 8. The results showed that S . Typhimurium challenge worsened ( P < 0.05) growth performance, S . Typhimurium load in intestinal digesta and visceral tissues, intestinal inflammatory responses, and permeability compared to the NC treatment. TMP supplementation increased ( P < 0.05) feed intake, weight gain, and feed efficiency by 4.3 to 12.0%, but decreased ( P < 0.05) S . Typhimurium load by 5.4 to 45.8%, inflammasomes (caspase-1/3/9, gasdermin A/E, and nod-like receptor protein 3) by 25.0 to 59.0%, chemokines (C-C motif ligand 2 and C-X-C motif 10) by 40.2 to 47.2%, intestinal permeability by 28.2% compared to the SC treatment. The TMP also reduced inflammatory response by influencing tumor necrosis factor α, interleukin 1β/4/6. Factorial analysis indicated that TMP and SC were interactive ( P < 0.05) on most parameters due to the more pronounced TMP effect in S. Typhimurium challenge groups. It is concluded that TMP can promote growth and mitigate S . Typhimurium infection by reducing the S . Typhimurium load and inflammatory response in broilers.